Pengembangan e-LKPD Berbasis Pendekatan Kontekstual Berbantuan Canva pada Materi Kimia Hijau di SMA: Penelitian - Nurliyana; Rayandra Asyhar; Afrida (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this research is to determine the development process, the feasibility according to media and material experts, teacher assessments, and student responses to the electronic student worksheets (e-LKPD) based on a contextual approach assisted by Canva on green chemistry material that has been developed.The research method used is Research and Development (R&D) with the Hannafin and Pack development model, which consists of 3 stages: Analysis, Planning, Development/Implementation.The instruments used were interview sheets and questionnaires.The data analysis techniques used are qualitative data analysis and quantitative data analysis.The results of this study indicate that the contextual approach-based e-LKPD on green chemistry material received feasibility validation from media experts with an average score of 4.7 and material experts with an average score of 4.7, both categorized as very feasible.Obtained an assessment by teachers with an average score of 4.6 in the very good category and student responses to the e-LKPD media with a percentage of 89.47% in the very good category.Based on the research results of developing e-LKPD using a contextual approach assisted by Canva on Green Chemistry material, this media is suitable for use as a learning medium in chemistry education.